2011
DOI: 10.1530/eje-10-0905
|View full text |Cite
|
Sign up to set email alerts
|

Expression of functional KISS1 and KISS1R system is altered in human pituitary adenomas: evidence for apoptotic action of kisspeptin-10

Abstract: Context: KISS1 was originally identified as a metastasis-suppressor gene able to inhibit tumor progression. KISS1 gene products, the kisspeptins, bind to a G-protein-coupled receptor (KISS1R, formerly GPR54), which is highly expressed in placenta, pituitary, and pancreas, whereas KISS1 mRNA is mainly expressed in placenta, hypothalamus, striatum, and pituitary. Objective and design: KISS1/KISS1R pituitary expression profile, coupled to their anti-tumoral capacities, led us to hypothesize that this system may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In mammals, Kiss1R activation is coupled to multiple intracellular signal transduction pathways [5]. However, as with Kiss1 effects on GnRH neurons, Kiss1 actions on pituitary gonadotrophs, somatotrophs and adenomas all involve increases in [Ca 2+ ] i [13,17,20,21,23]. In the present study, gKiss1 elevates [Ca 2+ ] i in goldfish pars distalis cells in a nifedipine-sensitive manner.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In mammals, Kiss1R activation is coupled to multiple intracellular signal transduction pathways [5]. However, as with Kiss1 effects on GnRH neurons, Kiss1 actions on pituitary gonadotrophs, somatotrophs and adenomas all involve increases in [Ca 2+ ] i [13,17,20,21,23]. In the present study, gKiss1 elevates [Ca 2+ ] i in goldfish pars distalis cells in a nifedipine-sensitive manner.…”
Section: Discussionmentioning
confidence: 49%
“…We also examined the interactions of gKiss1 10 with the two native goldfish GnRHs, salmon (s)GnRH (goldfish GnRH-3) and chicken (c)GnRH-II (goldfish GnRH-2) [48,49], on LH and GH release; these two GnRHs have been shown to be physiological neuroendocrine stimulators of both LH and GH secretion in this system [4,8,9]. Since Ca 2+ signalling and Ca 2+ entry through voltage-sensitive Ca 2+ channels (VSCCs) are important intracellular events in the neuroendocrine regulation of LH and GH release in goldfish [4,[7][8][9], and Ca 2+ mediates the actions of Kiss1 in many mammalian target tissues [23,28], we also tested the hypothesis that the hormone-releasing effects of gKiss1 10 are dependent on Ca 2+ entry via VSCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues were collected following the guidelines of the local committee on human research and immediately minced in RPMI-1640 medium (Invitrogen) under sterile conditions. Primary cultures were then prepared as described previously (Zatelli et al 2006, Martínez-Fuentes et al 2011. Informed consent of the patients was obtained for disclosing clinical investigation and performing the in vitro study.…”
Section: Tissue Collection and Primary Culturementioning
confidence: 99%
“…32 Since KP peptides are known to modify tumor cell behavior, 44,45 we tested the effects of KP 42−54 and KP 45−50 on the toxicity of Aβ 1−42 and PrP 106−126 in rat cortical neuron primary cell cultures. 32,33 The results showed that KP 42−54 and KP 45−50 caused a dose-dependent inhibition of 5 μM Aβ 1−42 toxicity, which was significant at concentrations above 2.5 μM ( Figure 3A).…”
mentioning
confidence: 99%